2011
DOI: 10.1007/s13105-010-0070-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antenatal, postpartum and post-weaning melatonin supplementation on blood pressure and renal antioxidant enzyme activities in spontaneously hypertensive rats

Abstract: Although melatonin lowers blood pressure in spontaneously hypertensive rats (SHR), its effect following antenatal and postpartum supplementation on the subsequent development of hypertension in SHR pups remains unknown. To investigate this, SHR dams were given melatonin in drinking water (10 mg/kg body weight/day) from day 1 of pregnancy until day 21 postpartum. After weaning, a group of male pups continued to receive melatonin till the age of 16 weeks (Mel-SHR), while no further melatonin was given to another… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 56 publications
(55 reference statements)
2
13
0
Order By: Relevance
“…5,9,30 Our results showed no significant difference in total SOD activity (Figure 1) or in the mRNA expressions of CuZn-SOD and Mn-SOD (Table 2) between SHR and WKY rats aged between 2 and 16 weeks. This has also previously been reported by Lee et al 22 Numerous other studies too have reported similar findings of unchanged SOD activity or its protein levels in the kidneys of adult SHR. 23,30,35 Renal morphology or urine protein excretion was not examined in this study.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…5,9,30 Our results showed no significant difference in total SOD activity (Figure 1) or in the mRNA expressions of CuZn-SOD and Mn-SOD (Table 2) between SHR and WKY rats aged between 2 and 16 weeks. This has also previously been reported by Lee et al 22 Numerous other studies too have reported similar findings of unchanged SOD activity or its protein levels in the kidneys of adult SHR. 23,30,35 Renal morphology or urine protein excretion was not examined in this study.…”
Section: Discussionsupporting
confidence: 89%
“…The main findings of this study include: (i) higher CAT activity and its relative mRNA levels in the kidneys of SHR from the age of 2 weeks (Figure 2 and Table 2), (ii) lower kidney GPx activity in SHR from the age of 3 weeks and lower relative GPx mRNA levels at 8 and 10 weeks of age ( Figure 3 and Table 2), (iii) higher renal TAS in SHR from the age of 3 weeks and onward (Table 3), (iv) higher renal MDA levels at 16 weeks (Table 3), (v) lower levels of renal H 2 O 2 in SHR from the age of 8 weeks (Table 4) and (vi) no significant difference in renal total SOD activity or the relative SOD mRNA levels of CuZn-SOD and Mn-SOD ( Figure 1 and Table 2) when compared with age-matched WKY rats. Although a significantly elevated renal CAT activity in 6-and 16-week old, 22 and older SHR 8,23 has been reported before, this is the first time that altered renal CAT expression and activity has been reported in pre-hypertensive SHR. The demonstration of higher CAT activity and its mRNA levels from as early as 2 weeks in SHR suggests that CAT expression and activity might be one of the primary abnormalities in SHR that might have a role in the pathogenesis of hypertension.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“… 43 It is also known to enhance the antioxidant activities of superoxide dismutase ( SOD ), glutathione peroxidase ( GPx ), catalase, and glutathione reductase (GR). 44 45 46 Besides this, melatonin has been shown to increase GPx protein in the kidney of spontaneously hypertensive rats (SHR), 47 and increase GPx-1 mRNA expression in human chorion, rat liver, and rat brain cortex. 48 49 50 Moreover, it also enhances the ability of cells to resist oxidative damage by inhibiting the pro-oxidant nitric oxide synthase.…”
Section: Discussionmentioning
confidence: 99%